Greenwashing in the IPO Process: The Urgency of Protecting Capital Market Investors - Bryant Zoe Faith (Transpublika Publisher, 2026)
The practice of greenwashing in initial public offerings (IPOs) poses a challenge to the Indonesian capital market, in line with the growing trend and demand for sustainable investment. Greenwashing involves the manipulation of a company’s environmental claims or performance to enhance its value and appeal to investors. The disclosure of misleading sustainability information has the potential to create information asymmetry and harm investors, whilst the regulations currently in force in the Indonesian capital market still contain legal loopholes that allow such practices to occur. The disclosure of misleading sustainability information may create information asymmetry and harm investors, while current Indonesian capital market regulations still contain legal loopholes that permit such practices. This normative legal study aims to analyse the urgency of protecting capital market investors against information asymmetry caused by pseudo-green claims during the IPO process. The findings indicate that neither the Law nor the Financial Services Authority Regulations explicitly regulate greenwashing practices in the IPO process; consequently, legal protection for investors against such practices remains inadequate. Therefore, this study recommends the reformulation of Financial Services Authority Regulation No. 51/POJK.03/2017 on the Implementation of Sustainable Finance to include provisions covering the IPO stage, strengthening standards and transparency in the disclosure of sustainability information through stricter verification requirements, and the establishment of an independent body authorised to audit and verify sustainability reports prior to an IPO. It is hoped that these recommendations will strengthen legal certainty, enhance investor protection, and foster a more transparent, accountable and equitable Indonesian capital market.